2011
DOI: 10.1111/j.1748-1716.2011.02312.x
|View full text |Cite
|
Sign up to set email alerts
|

Writer’s cramp: cortical excitability in tasks involving proximo-distal coordination

Abstract: In the dystonic group, facilitation of the FDI was observed during a task involving proximo-distal coordination. No differences in silent periods were observed when the muscle was activated alone. Our results suggest that such abnormal facilitation is not only an impairment of the central inhibitory mechanisms reported for dystonic patients, but, in addition, represents true abnormality in cortical muscle activation strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
(82 reference statements)
1
9
0
Order By: Relevance
“…In line with this, Tyč, Boyadjian, Allam and Brasil-Neto, in the paper presented in this issue (Tyč et al 2012), and in the accompanying paper published last year (Boyadjian et al 2011), for the first time, provided evidence for differential impairment of plasticity during the performance of various tasks, potentially dyskinesiogenic and neutral ones. In the paper published in this journal last year, Boyadjian et al (2011) showed, in a sample of writer's cramp patients, an abnormal increase in facilitation of a hand muscle (first dorsal interosseus) when a proximal muscle (deltoid) was co-activated, the feature that was not present during simple isolated activation of hand muscles. In this issue's paper, also dealing with writer's cramp patients, Tyč et al (2012) not only corroborated findings from previous studies on abnormal motor cortical representations of hand muscles, but by extending their investigation beyond the affected area, they showed that similar dysfunction exists in more proximal muscles, such as deltoid, as well.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…In line with this, Tyč, Boyadjian, Allam and Brasil-Neto, in the paper presented in this issue (Tyč et al 2012), and in the accompanying paper published last year (Boyadjian et al 2011), for the first time, provided evidence for differential impairment of plasticity during the performance of various tasks, potentially dyskinesiogenic and neutral ones. In the paper published in this journal last year, Boyadjian et al (2011) showed, in a sample of writer's cramp patients, an abnormal increase in facilitation of a hand muscle (first dorsal interosseus) when a proximal muscle (deltoid) was co-activated, the feature that was not present during simple isolated activation of hand muscles. In this issue's paper, also dealing with writer's cramp patients, Tyč et al (2012) not only corroborated findings from previous studies on abnormal motor cortical representations of hand muscles, but by extending their investigation beyond the affected area, they showed that similar dysfunction exists in more proximal muscles, such as deltoid, as well.…”
supporting
confidence: 53%
“…In line with this, Tyč, Boyadjian, Allam and BrasilNeto, in the paper presented in this issue (Tyč et al 2012), and in the accompanying paper published last year (Boyadjian et al 2011), for the first time, provided evidence for differential impairment of plasticity during the performance of various tasks, potentially dyskinesiogenic and neutral ones. In the paper published in this journal last year, Boyadjian et al (2011) showed, in a sample of writer's cramp patients, an abnormal increase in facilitation of a hand muscle (first dorsal interosseus) when a proximal muscle (deltoid) was co-activated, the feature that was not present during simple isolated activation of hand muscles.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…2006). Studying the muscle activity of the arm by EMG and transcranial magnetic stimulation, Boyadjian et al. (2011) found a change in proximo‐distal facilitation in the dystonic patients; i.e., compared to control, the cortical excitability was increased in the dystonic patients when the proximal muscle of the arm was activated concomitant with small muscles of the hand, adding complexity to the hypothesis about the diseased cortical excitability patterns.…”
mentioning
confidence: 99%
“…Changes in motoneuronal firing may give rise to compensatory adaptations in the cortical drive to motor neurones, including a changed excitability of inhibitory circuits controlling corticospinal output (Seifert & Petersen 2010). In a recent Acta Physiologica article, evidence was presented that Writer's cramp, a focal dystonia of the hand owing to repetitive, stereotyped writing movements, most likely involves an abnormal facilitation of these cortical inhibitory mechanisms (Boyadjian et al 2011).…”
mentioning
confidence: 99%